Preconception and pregnancy: opportunities to intervene to improve women's diets and lifestyles. (29th February 2016) - Barker, M.; Baird, J.; Lawrence, W.; Vogel, C.; Stömmer, S.; Rose, T.; Inskip, H.; Godfrey, K.; Cooper, C.
Abstract : Recently, large-scale trials of behavioural interventions have failed to show improvements in pregnancy outcomes. They have, however, shown that lifestyle support improves maternal diet and physical activity during pregnancy, and can reduce weight gain. This suggests that pregnancy, and possibly the whole periconceptional period, represents a 'teachable moment' for changes in diet and lifestyle, an idea that was made much of in the recent report of the Chief Medical Officer for England. The greatest challenge with all trials of diet and lifestyle interventions is to engage people and to sustain this engagement. With this in mind, we propose a design of intervention that aims simultaneously to engage women through motivational conversations and to offer access to a digital platform that provides structured support for diet and lifestyle change. This intervention design therefore makes best use of learning from the trials described above and from recent advances in digital intervention design.